TiO₂-supported dealuminated clinoptilolite: synthesis characterisation and kinetic studies for enhanced photo catalytic degradation of volatile organic compounds - Sanni, Saheed Olalekan (My University, 2014)
Advanced oxidation processes (AOPs) are supposedly effective means for removal of low concentration of organic pollutants from waste water as compared to conventional treatment methods. However, TiO2 metal semiconductor is the most promising photocatalyst for degradation of organic pollutant under heterogeneous photocatalysis as compared to other metal semiconductors. Challenges such as aggregation in solution, low adsorptive ability for non-polar organic contaminants and recycling are limitations in application of TiO2 for commercial purposes. The other limitations of TiO2, is it only utilizes 4-6% of the solar energy reaching the earth's surface which is in the UV region and also rapid electron-hole recombination due its wide band gap. In this work, the limitations are overcome by synthesis of a new photocatalyst material and further applied on degradation of model organic contaminants. The first part of this work focused on preparation and characterization of photocatalyst material. The photocatalyst synthesized were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray analysis (EDAX), Fourier transform infrared spectroscopy (FTIR), thermal gravimetric analysis (TGA) and UV-VIS diffuse reflectance spectrophotometer (DRUV-VIS). Supporting characterization techniques revealed partly dispersion of TiO2 within the cavities of dealuminated Clinoptilolite (HCP). TiO2 exist as nanoparticles or clusters on the HCP surface ascribed to lower loading of TiO2. XRD analysis showed that the support material employed was mainly Clinoptilolite and absorption band of prepared photocatalyst was red-shifted into the visible region, with slight reduction in band gap of photocatalyst. The second part focused on adsorption and photocatalytic degradation of methyl orange solution (MO) conducted under UV-irradiation in the presence of TiO2/HCP. The influence of operational parameters on degradation efficiency of photocatalyst material on MO was carried out in this study. Parameters such as initial dye concentration, pH, calcination temperature, inorganic anions and peroxide concentration were varied during degradation activities of MO. Comparative degradation efficiency of TiO2/HCP, TiO2 and HCP were conducted on dye mixture (Methyl orange and Methylene Blue) under UV irradiation. Kinetic analysis employing Langmuir-Hinshelwood model on dependencies of organic contaminants degradation was also conducted at different operational parameters. The adsorption capacity of MO was highest in the presence of TiO2/HCP at lower loading, which is ascribed to good dispersion of TiO2 on HCP and increased surface area of dealuminated Clinoptilolite. The photocatalytic degradation of methyl orange in the presence of TiO2/HCP was optimized at low dye concentration (30 ppm), acidic condition (pH 4), and calcination temperature of 873 K. Nitrate ion of Sodium salt accelerates degradation activities on methyl orange as compared to other inorganic anions. Photocatalytic degradation of methyl orange was greatly enhanced upon addition of oxidant (H2O2) and the photocatalyst possessed good repeatability after 3 cycles. TiO2/HCP exhibit highest degradation activities, followed by HCP as compared to TiO2 during the degradation of dye mixture. The degradation of MO by the photocatalyst fits into pseudo-first order kinetic model, while for comparative analysis of photocatalyst on dye mixtures follows second order kinetic model.
M. Tech. (Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Photocatalysts; Wastewater; Water purification; 628.166; Wastewater -- Purification.; Biodegradation; Microbial biotechnology; Water -- Purification